Headcount Constraint In An Event Organizing Company: Case Analysis Of Parteeboo - Arunasalam, Jaseetharaani (2014)
The purpose of this study was to explore the headcount constraint issue in SME event organizing and designing company ParteeBoo that caused them to turn down customer orders. ParteeBoo is a unique service provider that designs themed parties, especially children parties. It was established in February 2012 by two business partners. Hiring headcount based on peak season alone caused a dilemma to the business partners because of the impact on profit margin caused by lesser sales during non-peak season. Interviews were conducted with three ParteeBoo business partners, two interns and two customers to understand the issue faced by ParteeBoo.